we use equation 1 first.
-2x -y = -9
-y = -9 + 2x
y = 9 -2x
We substitute value of y in equation 2
5x - 2 (9 - 2x) = -9
5x -18 - 4x = -9
5x - 4x = -9 + 18
x = 18 -9
x = 9
We now find the value of y
-2x -y = -9
-2 (9) - y = -9
-18 - y = -9
-y = -9 + 18
y = 9 - 18
y = -9
To solve for x, you need to isolate/get x by itself in the equation:
Square ² both sides to get rid of the square root √
x - 2 = 0 Add 2 on both sides
x - 2 + 2 = 0 + 2
x = 2
Answer: x = 0
Step-by-step explanation:
4 + 3x - 4= 0
3x=0 (divide both sides by 3)
x= 0/3
x = 0
Step-by-step explanation:
Answer: Twenty-four minus the sum of six and three
Happy to help!
The answer is $426.1. Hope I could help! :D
2
3
Answer:
you have to use cross-multiplication in order to find out the answer to this question.
Step-by-step explanation:
9/12 times 2/3